181 A Phase-2 Sequential Parallel Comparison Design Study to Evaluate the Efficacy and Safety of Adjunctive Pimavanserin in Major Depressive Disorder. (April 2020) - Fava, Maurizio; Dirks, Bryan; Freeman, Marlene P.; Shelton, Richard C.; Thase, Michael E.; Trivedi, Madhukar H.; Papakostas, George I.; Liu, Keith; Whitworth, Troy; Stankovic, Srdjan
Abstract: Study Objectives: Depression is the leading cause of disability worldwide, with fewer than 50% of treated patients achieving full remission. This study ("CLARITY, " ACP-103-042: NCT03018340) examined the 5-HT2A inverse agonist pimavanserin (PIM) as a potential adjunctive treatment for major depressive disorder (MDD). Method: Adult female and male subjects with a DSM-5 primary diagnosis of a major depressive episode as part of MDD, inadequate response to ongoing SSRIs or SNRIs of adequate dose and duration as confirmed by the Massachusetts General Hospital Antidepressant Treatment History Questionnaire, and a MADRS total score >20 were randomized to PIM 34 mg/day or placebo (PBO) added to their SSRI/SNRI treatment. A sequential parallel comparison design was used, consisting of two 5-week stages. PBO nonresponders in Stage-1 who met prespecified criteria were re-randomized to PIM or PBO for the second period (Stage-2). The primary efficacy measure was the weighted average of Stage-1 and Stage-2 total scores of the HAMD-17. Results: Of the 207 patients enrolled, 52 received PIM, and 155 received PBO in Stage 1. Mean age was 46.2 years, and 72.9% of patients were female. Baseline MADRS total (mean [SD]: 31.5 [0.4]) and HAMD-17 total scores (22.2 [0.3]) indicated a moderate overall severity of illness. PIM met the primary endpoint, reducing the weighted Stage-1/Stage-2 HAMD-17 total score relative to PBO (least-square means [LSM] difference, –1.7; standard error [SE], 0.9; P=0.04). Stage-1 PIM patients demonstrated highly significant 5-week improvement on the HAMD-17 (LSM difference=–4.0, SE=1.1; P<0.001; effect size, Cohen's d: 0.626), separating from placebo by the end of Week 1 (LSM difference=–1.7, SE=0.8; P=0.04). Stage-2 results showed no significant separation among Stage-1 placebo nonresponders (P=0.69). In Stage 2, a substantively smaller number of subjects (n=58) were rerandomized than planned, likely due to restrictive criteria for re-randomization. Greater overall improvement was seen with PIM relative to PBO on the key secondary endpoint, the Sheehan Disability Scale (LSM difference=–0.8, SE=0.3; P=0.004), and positive results were also seen on 7 of the 11 other secondary endpoints, including responder rate (≥50% reduction in HAMD-17 total; P=0.007), Massachusetts General Hospital Sexual Functioning Index (P<0.001), and Karolinska Sleepiness Scale for daytime sleepiness (P=0.02). Discontinuations due to adverse events were low (PIM 1.2%, PBO 3.2%). One serious adverse event was reported in each treatment group, deemed unrelated to treatment. No deaths were reported. Laboratory assessments, electrocardiography, and changes in vital signs were unremarkable, and no new safety signals were reported. Conclusions: Study data provide evidence of the efficacy, safety, and tolerability of adjunctive PIM in treating MDD inadequately responsive to SSRI or SNRI therapy. Efforts to confirm these results are ongoing in a Phase 3 program. Funding Acknowledgements: ACADIA Pharmaceuticals Inc.